Pilomatrixoma of the Arm: A Rare Case with Cytologic Diagnosis - Ruchika Gupta; Sarika Verma; Pankaj Bansal; Anup Mohta (Case Reports in Dermatological Medicine)
Pilomatrixoma, a benign skin appendageal tumor, is seen commonly in head and neck. Occurrence of pilomatrixoma in the upper extremities is not common and has been reported infrequently in the available literature. Only a few cases with preoperative aspiration cytology have been reported in the literature. A five-year-old girl underwent fine needle aspiration (FNA) of a firm subcutaneous nodule on the lateral aspect of left arm. FNA smears showed scattered and few fragments of round to oval cells along with multinucleated giant cells. Few shadow cells were seen. A cytologic impression of pilomatrixoma was rendered, which was confirmed on histopathology. Pilomatrixoma, a common skin appendageal tumor in head and neck region, should be considered in the cytologic differential diagnoses of subcutaneous masses even in unusual locations like arm. The varied cytomorphology should be remembered to avoid misdiagnosis.